COLLABORATIVE GOVERNANCE DALAM PENYELENGGARAAN INFRASTRUKTUR JARINGAN UTILITAS DI KOTA TANGERANG - Syamsudin, AA Chaerul; Hardian, Dafyar Eliadi; Mulyadi, Edi (Perspektif : Jurnal Ilmu Administrasi, 2025)
This study examines Collaborative Governance in the Implementation of Utility Network Infrastructure in Tangerang City, focusing on the interaction between local government and the private sector in managing utility networks. This study uses a qualitative approach with data collection techniques through in-depth interviews with various stakeholders, including the Public Works and Spatial Planning Agency (PUPR), the Regional Development Planning Agency (Bappeda), the Investment and One-Stop Integrated Services Agency (DPMPTSP), the Transportation Agency, the Public Order Agency (Satpol PP), and representatives from private utility network providers. The results show that Collaborative Governance in the implementation of utility network infrastructure in Tangerang City faces various challenges, such as a lack of initial coordination, differences in regulatory interpretations, and obstacles in policy integration between agencies and the private sector. However, several strategies have been implemented to improve the effectiveness of collaboration, including improved cross-sector communication, regulatory alignment, and the use of digital technology in the planning and supervision of utility network infrastructure. The conclusion of this study emphasizes that the success of Collaborative Governance is highly dependent on the active involvement of all stakeholders, transparency in policies, and a shared commitment to maintaining the sustainability of utility network infrastructure. Therefore, a more structured and participatory approach is needed in the planning and implementation process to create a more efficient, inclusive, and sustainable utility network system in Tangerang City. Keywords: Collaborative Governance, Utility Network Infrastructure, Tangerang City